EXPERIMENT ON THE FEEDING OE FRY OF CATFISH HETEROPNEUSTES FOSSILIS - Huq, Molla F; Huque, M K Inamul; Haque, A K M Inamul (Indian Journal of Fisheries, 2011)
An experiment was conducted to determine a suitable feed for the fry of catfish, Heteropneustes fossilis. Of the six types of feed tried, 5 had a common base of vegetable origin. The feeds diflfered only in their animal protein components. Feed I (with meat oflfal and fish meal) and Feed II (with meat offal and blood meal) and Feed III (with lysine-cum-methionine) gave the best results. Feed consisting of only fish meal with no vegetable base resulted in weight reduction of the fry